Pendampingan Dan Bimbingan Teknis Pembuatan Es Krim Dari Susu Kambing Bagi Kelompok Perempuan Produktif Di Desa Banyumulek Kecamatan Kediri-Lombok Barat - Baiq Rani Dewi Wulandani; Djoko Kisworo; Fahrullah; Bulkaini; Wahid Yulianto; Haryanto (Universitas Mataram, 2025)
Based on discussions and consultations with community partners, utilizing goat milk to create simple and easy-to-produce processed products is essential for enhancing the partners' skills in processing goat milk. The priority is to transform it into a product that holds practical value. The goal of this community service activity is to provide benefits by offering training that improves the partners' knowledge and skills, particularly in processing, packaging, and labeling, allowing the product to have its own packaging and brand. This enables the business group to gain new knowledge and generate income for the partner families. Furthermore, the activity serves as an initiative to form a new business group focused on developing goat milk-based ice cream production. The methods used in this community service activity include demonstration and participatory approaches. Facilitators and technicians directly demonstrated the process of making goat milk ice cream, along with technical guidance on the product packaging process. The results show that the partners have gained the ability to produce ice cream that complies with ASUH standards (safe, healthy, intact, and halal). They have successfully maintained the quality of raw materials and additives, and achieved an optimal balance in the ingredient ratios. The ice cream packaging process has been effective in preventing issues such as leakage or damage during storage and distribution. However, the partners still require further technical guidance on production planning, including determining product types, quantities, production schedules, quality control, equipment needs, team management, and using social media platforms to promote the products. Additional support is needed in pricing strategies, value-added calculations, and setting profit margin targets. In conclusion, the activity demonstrates the potential for product development through proper ingredient formulation and optimal production processes. Recommendations include refining ingredient composition for desired taste and texture, determining appropriate process variables, and developing new ice cream variants to increase market value